PENGARUH USER EXPERIENCE (UX) DALAM PENGEMBANGAN SISTEM INFORMASI MANAJEMEN PADA PERUSAHAAN TEKNOLOGI - Rahma Aulia; Muhammad Irwan Padli Nasution (CV. Barokah Publsiher, 2025)
User Experience (UX) is a fundamental aspect in the development of Management Information Systems (MIS), especially because the quality of the user experience greatly determines the level of acceptance and success of a system's implementation. UX includes user perceptions of ease of direction, comfort when communicating and the appearance of the interface, and the system's usability in supporting work needs. This study aims to deeply reduce how the quality of UX has a significant influence on the development and performance of MIS. The main focus of the study is directed at three main indicators, namely the level of satisfaction with use (usability), the level of user satisfaction, and the system's usability in supporting managerial activities and decision-making. The results of the analysis show that MIS with good UX design can improve the smoothness of the workflow, reduce the burden on user perception, and accelerate the process of understanding the available features. In addition, a positive user experience encourages the usability of MIS in providing precise, accurate, and easily accessible information, thereby increasing overall organizational productivity.